PENGARUH GROWTH OPPORTUNITY, FIRM SIZE, PROFITABILITAS, LIQUIDITY, DAN FIRM QUALITY TERHADAP DEBT MATURITY STRUCTURE (Studi Pada Perusahaan Manufaktur Di BEI Tahun 2013-2018)ENGARUH GROWTH OPPORTUNITY, FIRM SIZE, PROFITABILITAS, LIQUIDITY, DAN FIRM QUALITY TERHADAP DEBT MATURITY STRUCTURE (Studi Pada Perusahaan Manufaktur Di BEI Tahun 2013-2018) - Zulfikar, Reno; Arfianto, Erman Denny (Diponegoro Journal of Management, 2020)
Capital structure plays an important role in corporate financial management. Debt is an essential part of the capital structure. Once firms use debt, firms need to consider their debt maturity structure. Thus, study analyzed the factors that influence debt maturity structure.Â Research population used all publicly traded manufacturing companies in Indonesia listed on Indonesia Stock Exchange (IDX) during 2013-2018. The samples observed in total were 108 samples. The analytical method of this study used multiple linear regression.The results showed firm size and liquidity hadÂ  positive significant effect on debt maturity structure. Profitability had negative significant effect on debt maturity structure. Meanwhile, growth opportunity and firm quality had positive insignificant effect on debt maturity structure.